(untitled) (Medico Legal Update, 2021)
Indian roads are deemed to be the most dangerous, considering the number of annual fatalities, which touched 151,113 in the year 2019, the highest in the world. Causes ranging from poorly designed roads, tardy enforcement of traffic rules, delay in giving medical assistance, ill equipped hospitals, refusal of treatment by hospitals, all contribute to this unenviable predicament. A lax regulatory environment with minor penalties, has accentuated the crisis. Having held the pivotal position amongst 199 countries, there is a dire need for concrete action by Government. While 2,211,439 road accidents in the US in the year 2016 took away 37,461 lives,a relatively lower number of 480,652 accidents snuffed out 150,785 lives in India. Creating comparable safety levels could take decades for a developing country. But with the country’s share constituting about 11% of road accident casualties worldwide and the estimated social cost hovering around 58 billion, the problem begs for an immediate fix. Tightening regulations would be a practical solution for both short and long-term gains. Enough deterrents need to be put in rules governing road safety; the Motor Vehicles Act to ensure defensive driving. This paper examines how certain loopholes need to be plugged in the new Motor Vehicles Act 2019 to achieve the higher goal of road safety